PENGARUH KESEIMBANGAN KEHIDUPAN KERJA, KETERLIBATAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI BADAN KEUANGAN DAN ASET DAERAH KABUPATEN KONAWE SELATAN - K.M Isran; Alida Palilati; Sri Wiyati Mahrani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
The purpose of this study was to examine and analyze the effect of work-life balance, interaction and leadership style on employee performance. This study uses a survey approach with an explanatory research design. the samples used in this research are 49 people. Sampling carried out by means of a census, Method of data collection use questionnaires. Data analysis use descriptive analysis and multivariate regression analysis. The results showed that work-life balance, work interaction and leadership simultaneously had a positive and significant effect on employee performance. Work-life balance partially positive and significant effect on employee performance. Partial work involvement has a positive and significant effect on employee performance. Leadership style has a positive and significant effect on improving employee performance. The value of the coefficient of determination is 0.972, which means that the ability of the work-life balance variable, work interaction and leadership style in the employee performance variable is 97.2%, while the remaining 2.8% is influenced by other variables not included in this study.